2016
DOI: 10.4274/jcrpe.2819
|View full text |Cite
|
Sign up to set email alerts
|

Indices of Glucose Homeostasis in Cord Blood in Term and Preterm Newborns

Abstract: Objective:According to the thrifty phenotype hypothesis, intrauterine malnutrition has a role in the etiology of type 2 diabetes. This study was planned to determine the early alterations in indices of glucose homeostasis (glucose, insulin, and cortisol) in term and preterm newborns and the correlations of glucose, insulin, and cortisol levels with insulin resistance indices.Methods:A descriptive study comprising 35 term and 35 preterm newborns was carried out from December 2013 to June 2015. Venous cord blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…While Insulin has a direct relation with HOMA-IR, cortisol was negatively associated with HOMA-IR in both FT and PT newborns. In agreement to our research, Ahmad et al, noticed that the mean cord blood glucose and cortisol levels in FT newborns were significantly higher than those in PT infants, while HOMA-IR and Insulin levels were found more in PT newborns than in FT newborns [18].Therefore, the disruption of the insulin signal transduction leads to hyperinsulinemia and insulin resistance [5,19] .…”
Section: Sensitivitysupporting
confidence: 90%
“…While Insulin has a direct relation with HOMA-IR, cortisol was negatively associated with HOMA-IR in both FT and PT newborns. In agreement to our research, Ahmad et al, noticed that the mean cord blood glucose and cortisol levels in FT newborns were significantly higher than those in PT infants, while HOMA-IR and Insulin levels were found more in PT newborns than in FT newborns [18].Therefore, the disruption of the insulin signal transduction leads to hyperinsulinemia and insulin resistance [5,19] .…”
Section: Sensitivitysupporting
confidence: 90%
“…In the group of 35 AGA term newborns and 35 AGA pre-term newborns, Ahmad studied: insulin, glucose, HOMA IR, Quicki in umbilical cord blood, based on an enzymatic method and ELISA. He showed higher insulin concentrations in AGA preterm compared with AGA term children [ 2 ]. Markopoulou emphasised that adults (> 18 years old) born as AGA preterm would represent metabolic syndrome and cardiac disorders in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Results of a study conducted between 2004 and 2007 in the group of 118 Polish children with SGA confirmed scientific reports on the risk of insulin resistance [ 1 ]. Numerous papers report the occurrence of insulin resistance also in the group of children born preterm with normal weight for a given gestational age (AGA – appropriate for gestational age) and for sex [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we found significant differences between the HOMA-IR, an estimation of IR, when using the CV compared with CA blood. Many studies have utilized HOMA-IR calculated from CV or mixed cord blood to estimate fetal IR 21,22 ; however, none to our knowledge has directly compared HOMA-IR calculated from CA compared with CV blood. Our findings in the CA blood are consistent with the findings from the Merida study which calculated HOMA-IR from CA blood of 197 healthy neonates.…”
Section: Discussionmentioning
confidence: 99%